Contribution of the geographic information system for groundwater to the mapping of subterranean waters in the region Djelfa (Algeria) - Koussa, Miloud; Bouziane, Mohamed-Tewfik (Journal of Applied Engineering Science & Technology; Vol 3 No 2 (2017), 2017)
The Djelfa region characterized by a semi-arid climate. The quality of groundwater is among the problems that are becoming increasing concern in the region. The physico-chemical characteristics of water are severely affected by high salinity of them. This research is devoted to the use of geographic information systems GIS, for drawing maps of the main parameters that can reveal the spatial variation of physical and chemical characteristics of water to achieve a good estimate of its quality. Mapping is the first step in the creation of geographic information systems. The aim of our work is to present a tool for decision making that can establish useful maps to study the water quality of the Djelfa region.